2017
DOI: 10.1186/s12893-017-0269-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic foreign body ingestion in pediatric patients: report of three cases

Abstract: Background: Although foreign bodies (FBs) typically pass spontaneously and uneventfully through the digestive tract, a subset of such bodies may become trapped, eventually leading to significant injury. In particular, the ingestion of magnetic materials can cause serious morbidity due to proximate attraction through the intestinal wall. Case presentation: We recently treated three pediatric patients who had ingested several magnetic foreign materials. None of these patients exhibited any clinical symptoms or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 10 publications
0
26
0
6
Order By: Relevance
“…However, none of the patients experienced a sudden abdominal emergency requiring an acute operation. 4 The specific properties of MFBs, the increasing incidence of their ingestion and possible serious complications have contributed to the creation a separate care algorithm. This algorithm was published by Sola et al in 2018 and suggested that the most endangered group of patients are those who swallow multiple MFBs or have a combination with of other magnetizable objects that should be observed during a hospitalization with repeated clinical and X-ray examinations followed by an endoscopic and/or surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the patients experienced a sudden abdominal emergency requiring an acute operation. 4 The specific properties of MFBs, the increasing incidence of their ingestion and possible serious complications have contributed to the creation a separate care algorithm. This algorithm was published by Sola et al in 2018 and suggested that the most endangered group of patients are those who swallow multiple MFBs or have a combination with of other magnetizable objects that should be observed during a hospitalization with repeated clinical and X-ray examinations followed by an endoscopic and/or surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…1) which was based on the guidelines and the actual experiences at our center. For patients with perforation and stula found after endoscopic removal, the general treatment is to switch to surgery 14 . However, one patient in this study had a stula from the lower esophagus to the cardia.…”
Section: Discussionmentioning
confidence: 99%
“…In a report, delayed diagnosis (longer than two days from ingestion) and treatment were related with a worse outcome [ 5 ]. The symptoms usually appear between 1 and 7 days after ingestion [ 12 ], but some authors reported delayed diagnosis of ingested foreign body in a child with intermittent abdominal pain of 6 months [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, powerful and small rare-earth magnets have been manufactured and incorporated into toys, thus increasing the risk of ingestion of dangerous material [ 4 ]. Most of FBs pass through the gastrointestinal tract uneventfully; however, in rare cases, their shape and size can cause complications such as obstruction, ischemia, perforation, or fistula [ 5 ]. Endoscopic intervention is required in 10–20% of patients, while only 1% of patients need urgent surgical approach [ 6 ].…”
Section: Introductionmentioning
confidence: 99%